Alejandro Torres Gutiérrez, Minorías y Multiculturalidad en Austria, Madrid, Dykinson, Universidad Carlos III, 2007 - Palomino, Rafael (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2008)
Sin resumen